On providing sink anonymity for wireless sensor networks. Issue 2 (3rd December 2010) - Ngai, Edith C.‐H.
Abstract: Sinks usually broadcast their addresses for data collection in sensor networks. However, this common operation opens up vulnerability for adversary to attack the sinks and obstruct their normal functions. In this paper, we suggest sink anonymity as a novel approach for data collection, which protects the privacy of the sinks and avoids them from becoming the target of attacks. We provide sink anonymity by omitting the address of the sink in routing, so that the identity and location of the sink are kept private. Our proposed Randomized Routing with Hidden Address (RRHA) scheme prevents the attackers from obtaining the receiver address by capturing the destination field of the packets or predicting the location of the sinks by observing the flow of network traffic. We examined the successful delivery rate, packet travel delay, and protection strength of our proposed scheme by both analysis and simulations. Copyright © 2010 John Wiley & Sons, Ltd. Abstract : We provide sink anonymity in wireless sensor networks to hide the identity and location of the sinks from passive attackers. We propose Randomized Routing with Hidden Address (RRHA) scheme, which omits the header field of destination address in routing. It prevents the attackers from obtaining the receiver's address by capturing the packets or predicting the locations of the sinks by observing the network traffic.